Supply Chain Information System Operations Model for Research Management for Asean University Network Quality Assurance at Institution Level - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The research supply chain Information System operations model for research management for asean university network quality assurance at institution level. The purposes of research study were design and to evaluate supply Chain Information System operations model for research management for asean university network quality assurance at institution level .The sample group in this study consisted of ten experts consisted five experts on supply chain , three experts on information technology and two experts on research. The research findings show that supply Chain Information System operations model for research management for asean university network quality assurance at institution level comprises five main components, namely, main components, suppliers , university , customers and consumers. Evaluation results by the ten experts show the evaluation rating mean of 3.63 with standard deviation of 0.81 that mean supply chain Information System operations model for research management for asean university network quality assurance at institution level and can support sustainable Information system development.